1986
DOI: 10.1254/jjp.42.425
|View full text |Cite
|
Sign up to set email alerts
|

Contractile Effects of Jellyfish Toxin Extracted from Carybdea rastonii on Isolated Rabbit Aorta

Abstract: Abstract-Effectsof the toxic component of jellyfish (Carybdea rastonii) (pCrTX) on the smooth muscle tension of isolated rabbit thoracic aorta were examined. pCrTX, at concentrations higher than 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A partially purified toxin (pCrTX) from the tentacles of the Japanese Carybdea rastonii contracted aortic strips which were attributed to the release of endogenous catecholamines and to an influx of Ca ++ in smooth muscle (Azuma et al 1986a). A portion of such contraction was attributed to release of prostaglandins and a direct effect on smooth muscle not dependent on Ca ++ influx (Ozaki et al 1986). The toxin also contracted intestinal smooth muscle which was attributed to release of prostaglandins (Nagase et al 1987).…”
Section: Venommentioning
confidence: 99%
“…A partially purified toxin (pCrTX) from the tentacles of the Japanese Carybdea rastonii contracted aortic strips which were attributed to the release of endogenous catecholamines and to an influx of Ca ++ in smooth muscle (Azuma et al 1986a). A portion of such contraction was attributed to release of prostaglandins and a direct effect on smooth muscle not dependent on Ca ++ influx (Ozaki et al 1986). The toxin also contracted intestinal smooth muscle which was attributed to release of prostaglandins (Nagase et al 1987).…”
Section: Venommentioning
confidence: 99%
“…As early as 1973, Calton and Burnett found the effect of two jellyfish toxins on calcium ion transport [ 35 ]. Since from 1983, the Ca 2+ antagonists verapamil, diltiazem and nifedipine were sequentially reported to antagonize cardiotoxicity of the venom from Chironex fleckeri [ 36 ], Portuguese man-o’war ( Physalia physalis ) [ 37 ], Carybdea rastonii [ 38 , 39 ] or C. capillata [ 33 ]. However, another study reported that the verapamil had no effect on Ca 2+ influx whilst La 3+ , a non-specific channel and pore blocker, inhibited the Ca 2+ influx, consistent with the presence of a pore-forming toxin existing in the venoms which was demonstrated by transmission electron microscopy in the case of C. fleckeri [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of adrenergic system in the cardiovascular toxicity of jellyfish venom was firstly drew by the partial inhibition of the α-adrenergic antagonist phentolamine, the central antiadrenergic reagent trifluoperazine as well as the phosphodiesterase inhibitor papaverine on the aorta contraction induced by the venom of the jellyfish C. rastonii [ 39 ]. Further studies showed that the α1-adrenergic antagonist prazosin and β-adrenergic blocker propranolol attenuated the nematocyst venom-induced pressor response and tachycardia in anaesthetized rats [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Ca 2+ antagonists verapamil, diltiazem, and nifedipine have all been shown to reduce the cardiotoxicity of venom from Physalia physalis (hydrozoan) [ 35 ], Carybdea rastonii (cubozoan) [ 36 , 37 ], Chironex fleckeri (cubozoan) [ 38 ], and Cyanea capillata [ 39 ]. Another study, however, found that verapamil did not affect Ca 2+ influx, but it was inhibited by La 3+ , a non-specific channel and pore blocker.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The adrenergic system also seems to play a role in the cardiovascular toxicity of jellyfish venom. This was first demonstrated when the aorta contraction induced by Carybdea rastonii (cubozoan) venom was inhibited by trifluoperazine and phentolamine [ 37 ]. Further research revealed that prazosin and propranolol reduced the tachycardia and venom-induced pressor response in anesthetized rats [ 49 , 50 ].…”
Section: Pathophysiologymentioning
confidence: 99%